From I DO to I DON’T: Recognition of Foreign Divorce in the Philippines - Christian George Melitante (Universitas Katolik Indonesia Atma Jaya, 2026)
The Philippines, uniquely situated as the only nation outside Vatican City where divorce remains illegal for the vast majority of its citizens, holds marriage in high legal and cultural regard. Marriage is enshrined in both the 1987 Constitution and the Family Code as an